Annexin A1-derived peptide Ac2-26 in a pilocarpine-induced status epilepticus model: Anti-inflammatory and neuroprotective effects - Gimenes, Alexandre D. (2019)
Background: The inflammatory process has been described as a crucial mechanism in the pathophysiology of temporal lobe epilepsy. The anti-inflammatory protein annexin A1 (ANXA1) represents an interesting target in the regulation of neuroinflammation through the inhibition of leukocyte transmigration and the release of proinflammatory mediators. In this study, the role of the ANXA1-derived peptide Ac2-26 in an experimental model of status epilepticus (SE) was evaluated. Methods: Male Wistar rats were divided into Naive, Sham, SE and SE+Ac2-26 groups, and SE was induced by intrahippocampal injection of pilocarpine. In Sham animals, saline was applied into the hippocampus, and Naive rats were only handled. Three doses of Ac2-26 (1 mg/kg) were administered intraperitoneally (i.p.) after 2, 8 and 14 h of SE induction. Finally, 24 h after the experiment-onset, rats were euthanized for analyses of neuronal lesion and inflammation. Results: Pilocarpine induced generalised SE in all animals, causing neuronal damage, and systemic treatment with Ac2-26 decreased neuronal degeneration and albumin levels in the hippocampus. Also, both SE groups showed an intense influx of microglia, which was corroborated by high levels of ionised calcium binding adaptor molecule 1(Iba-1) and monocyte chemoattractant protein-1 (MCP-1) in the hippocampus. Ac2-26 reduced the astrocyte marker (glial fibrillary acidic protein; GFAP) levels, as well as interleukin-1β (IL-1β), interleukin-6 (IL-6) and growth-regulated alpha protein (GRO/KC). These effects of the peptide were associated with the modulation of the levels of formyl peptide receptor 2, a G-protein-coupled receptor that binds to Ac2-26, and the phosphorylated extracellular signal-regulated kinase (ERK) in the hippocampal neurons. Conclusions: The data suggest a neuroprotective effect of Ac2-26 in the epileptogenic processes through downregulation of inflammatory mediators and neuronal loss.